Fournier's Gangrene of the Penis following a Human Bite Wound. (25th October 2018) - Overholt, Tyler; Hajiran, Ali; Ueno, Cristiane; Zaslau, Stanley
Abstract : Fournier's gangrene isolated to the penis is exceedingly rare. It is an urologic emergency that requires emergent parenteral antibiotics as well as aggressive irrigation and debridement. While human bite wounds can be overlooked as a serious cause of injury and infection, they can result in highly dangerous, polymicrobial infections in affected patients. Here, we report a case of penile Fournier's gangrene caused by a human bite wound managed with broad spectrum antibiotics, irrigation and debridement, penile reconstruction, and skin grafting with successful preservation of a normal penile structure and function.